Effective factors in developing students’ monologic speech - Muminova, Oydin Qurbonovna (The Lingua Spectrum, 2026)
This article provides a comprehensive scientific and pedagogical analysis of the systematic organization of the literary reading process and the effectiveness of specialized pedagogical technologies in enhancing the monologic speech of higher education students. The relevance of the research is determined by the necessity of developing Uzbek language speech competencies in students not merely through theoretical knowledge, but by deeply understanding the essence of a literary work, perceiving it emotionally, and transferring the derived conclusions into live speech processes in the era of globalization. Modern educational standards require students not only to receive information but also to process it analytically and present it as independent thought. The instructor proposes a unique staged system for organizing literary reading: this process begins with providing preliminary information about the work and its author, continues with working on the active and passive vocabulary of the text, involves analyzing subtextual meanings through questioning, and concludes with the expression of a personal-critical attitude toward the work in the form of a monologue. The complex of interactive exercises presented in the article serves to systematically develop students’ skills in articulating their thoughts in the state language in a consistent, logical, and creative manner, while also enriching their vocabulary. The obtained scientific and practical results indicate that the synthesis of literary analysis and speech activity significantly increases students’ intrinsic motivation for language learning. This approach strengthens the skill of creating independent texts and presenting them before an audience – the highest and most complex stage of speech activity. The research findings can serve as a practical recommendation for improving lesson efficiency in the fields of philology and pedagogy in higher education.